Ceftazidime–avibactam for the Treatment of Intra-abdominal Sepsis and Urosepsis: A Retrospective Hospital-based Study in India - Prachee Sathe; Chitra Lele; Simran Chandra; Tatyasaheb Jadhav; Durgesh Makwana; Devidas Bhalerao (International Journal of Advanced Medical and Health Research)
Background: In India, microbial susceptibility to antibiotics has been gradually decreasing, thus making treatment of multidrug-resistant bacterial infections challenging. We aimed to assess the effectiveness of ceftazidime–avibactam in patients with intra-abdominal sepsis or urosepsis. Methods: This hospital-based, single-center retrospective study was conducted between April 2020 and March 2022 using data from inpatient records. Outcomes included inpatient mortality, clinical success/failure, and microbiological cure/failure measured on day 14/end of treatment, length of hospitalization and intensive care unit (ICU) admission, treatment and infection characteristics, recurrence within 30 days, and healthcare resource utilization. Descriptive statistics were used for data analysis. Results: Data from 46 patients (mean age = 65.2 ± 14.5 years, 73.9% male) were included. Ceftazidime–avibactam treatment was initiated within 5 days of hospitalization in 51.2% of patients. The median (range) duration of treatment was 8 (1, 20) days, and the average daily dose was 4.6 g. Inpatient and 30-day all-cause mortality rates were 41.5% and 17.1%, respectively. We observed clinical success, defined a priori, by day 14 in 58.5% of patients and microbiological cure in 61.3%. Most patients (97.0%) did not have recurrent infections. The median (range) length of hospitalization and ICU admission was 15.5 (3, 63) days and 11 (2, 63) days, respectively. Most patients (85.7%) utilized various healthcare resources during hospitalization. Conclusion: Among patients with available data, most showed clinical success (58.5%) and microbiological cure (61.3%) within 14 days of treatment initiation with ceftazidime–avibactam, with nearly no recurrence of infection, indicating treatment effectiveness in patients with intra-abdominal sepsis or urosepsis in an Indian hospital setting.